How to make experimental economics research more reproducible: lessons from other disciplines and a new proposal - Maniadis, Zacharias; Tufano, Fabio; List, John A. (Emerald Group Publishing Limited, 2015)
Efforts in the spirit of this special issue aim at improving the reproducibility of experimental economics, in response to the recent discussions regarding the “research reproducibility crisis.” We put this endeavour in perspective by summarizing the main ways (to our knowledge) that have been proposed – by researchers from several disciplines – to alleviate the problem. We discuss the scope for economic theory to contribute to evaluating the proposals. We argue that a potential key impediment to replication is the expectation of negative reactions by the authors of the individual study, and suggest that incentives for having one’s work replicated should increase.